MicroRNAs and Alzheimer's Disease Mouse Models: Current Insights and Future Research Avenues. (31st July 2011) - Delay, Charlotte; Hébert, Sébastien S.
Abstract : Evidence from clinical trials as well as from studies performed in animal models suggest that both amyloid and tau pathologies function in concert with other factors to cause the severe neurodegeneration and dementia in Alzheimer's disease (AD) patients. Accumulating data in the literature suggest that microRNAs (miRNAs) could be such factors. These conserved, small nonprotein-coding RNAs are essential for neuronal function and survival and have been implicated in the regulation of key genes involved in genetic and sporadic AD. The study of miRNA changes in AD mouse models provides an appealing approach to address the cause-consequence relationship between miRNA dysfunction and AD pathology in humans. Mouse models also provide attractive tools to validate miRNA targets in vivo and provide unique platforms to study the role of specific miRNA-dependent gene pathways in disease. Finally, mouse models may be exploited for miRNA diagnostics in the fight against AD.